CONDITIONS FOR THE RETURN OF LABOR MIGRANTS TO UKRAINE - Оксана Володимирівна Захарова (Збірник наукових праць Черкаського державного технологічного університету: Серія: Економічні науки, 2019)
The purpose of the article is the theoretical definition and statistical justification of the conditions for the return of labor migrants to Ukraine. Scientific novelty consists in substantiating the procedure for diagnosing a person's decision on employment outside the country and formalizing the conditions for increasing the interest of citizens of Ukraine in finding employment on its territory. It is established that the desire for an adequate standard of living is natural for a person regardless of time, territory of residence, gender, nationality and religion. A diagram has been developed for diagnosing the probability of a person making a decision on employment outside the country, based on eleven of the most relevant criteria, for each of which four situations most often encountered in life are given. An algorithm has been developed for a person to make a final decision on the feasibility of employment outside the country. A generalized formula is proposed that describes the possibilities of increasing Ukrainian interest in employment in the country's labor market and the return of Ukrainian labor migrants to their homeland. Three main factors underlying the person’s decision on the place of employment are substantiated and the current state is analyzed according to the trends of each of these factors. Further research should be aimed at theoretical justification and methodological support of the processes of appropriation and dissemination of experience gained by Ukrainian labor migrants outside the country in the Ukrainian economy in order to obtain sustainable development trends.